2001
DOI: 10.1016/s0893-133x(01)00298-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Affinity of Duloxetine and Venlafaxine for Serotonin and Norepinephrine Transporters in vitro and in vivo, Human Serotonin Receptor Subtypes, and Other Neuronal Receptors

Abstract: The blockade of serotonin (5-HT) and norepinephrine (NE) transporters in vitro and in vivo by the dual 5-HT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
306
4
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 655 publications
(321 citation statements)
references
References 30 publications
4
306
4
7
Order By: Relevance
“…Serotonin neuronal pathways are involved in the mechanism of action of antidepressant medications and there is considerable evidence that they are involved in the pathogenesis of depression (65)(66)(67). The functional role of 5-HT in the immune system has come under increasing investigation as neuroscientists and immunologists have begun to study the underlying biology that is common to the central nervous system and the immune system (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin neuronal pathways are involved in the mechanism of action of antidepressant medications and there is considerable evidence that they are involved in the pathogenesis of depression (65)(66)(67). The functional role of 5-HT in the immune system has come under increasing investigation as neuroscientists and immunologists have begun to study the underlying biology that is common to the central nervous system and the immune system (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to in vitro and in vivo studies that showed that systemic administration of duloxetine resulted in penetration into the brain and inhibition of NET. 6,10 Administration of tyramine demonstrated the functional effect of impaired NE reuptake. The administration of duloxetine resulted in a linear dose-dependent increase in the amount of tyramine required to cause an increase of 30 mm Hg systolic blood pressure (PD 30 ) from 120 mg/d.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo binding of [ 3 H]-nisoxetine to the NE transporters was evaluated as previously described by Bymaster et al 6 All assays were performed in triplicate. Nonspecific binding was determined by including 10 mol/L desipramine.…”
Section: Ex Vivo Bindingmentioning
confidence: 99%
“…Duloxetine hydrochloride, a potent serotonin (5-HT) and norepinephrine reuptake inhibitor (8), has been approved for the management of diabetic peripheral neuropathic pain (DPNP) and for the treatment of major depressive disorder. In all three placebo-controlled trials conducted in patients with DPNP, duloxetine demonstrated efficacy in reducing pain severity in patients with DPNP at 60 mg once daily and twice daily (9 -11).…”
mentioning
confidence: 99%